Acehnese Dayah Ulama's Response to the Use of 'Urf in Istinbath of Fiqh Law from Islam Nusantara - Yusuf, Januddin Muhammad; Yuslem, Nawir (Institut Agama Islam Negeri Curup, 2023)
This study aims to find the reaction or response of Acehnese dayah scholars (ulama) to the use of ‘urf in istinbath of Fiqh Law from Islam Nusantara. This study departs from the fact that Islam is a religion of rahmatan lil’alamin as a universal religion, and the development of society in Indonesia has a growing variety of cultures, thus requiring a special fiqh methodology in adapting culture to religion. This research is a field research with a descriptive qualitative research type. Data collection techniques using documentation, observation and interview techniques. The interviewees came from several dayah clerics who are members of several Islamic organizations such as the NU organization, the MPU organization, the HUDA organization, and the Tastafi Aceh organization. The results of the study show that the response of Islamic religious scholars in Aceh to the use of ‘urf in istinbath fiqh law of Islam Nusantara, some accepted and some refused. Those who refused reasoned that the use of ‘urf fashid is not in accordance with the Shari'a and leads to shirk as is customary of peulheuh alen, rabu abeh in Acehnese society. While the use of ‘urf shahih, Islamic religious scholars in Aceh accept it because it does not conflict with the Shari'a like khanduri blang because it is included in the generality of the argument for charity. Thus, it can be concluded that the istinbath method of Islam Nusantara fiqh law can be accepted and has its legality according to Acehnese Islamic scholars when using ‘urf shahih. The findings of this study contribute to the fact that customary practices need to be preserved if they do not conflict with Shari'a.